2020
DOI: 10.1002/jso.25888
|View full text |Cite
|
Sign up to set email alerts
|

Log odds of positive lymph nodes predicts survival in patients treated with neoadjuvant therapy followed by esophagectomy

Abstract: Background and Objectives: We aimed to evaluate the efficacy of the log odds of positive lymph nodes (LODDS) in survival prediction of patients with esophageal carcinoma receiving neoadjuvant therapy, compared with N descriptor and positive lymph node ratio (LNR). Methods: Patients with esophageal carcinoma receiving neoadjuvant therapy from 2004 to 2015 were reviewed in Surveillance, Epidemiology, and End Results database. The receiver operating characteristics curve and area under the curve (AUC) were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 32 publications
(53 reference statements)
1
14
0
Order By: Relevance
“…Pei et al 24 reported that LODDS showed the best accurate ability to predict the survival of CRC patients. Ye et al reported similar results in esophageal carcinoma, demonstrating that the prognostic efficacy of LODDS is superior to that of the N descriptor and LNR for estimating OS 25 . We showed that LCC patients were more in LODDS ≥ −0.9 sub, which might be related to the different sensitivity to immunotherapy between LCC and RCC, and this was not observed in N stage and LNR subs.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Pei et al 24 reported that LODDS showed the best accurate ability to predict the survival of CRC patients. Ye et al reported similar results in esophageal carcinoma, demonstrating that the prognostic efficacy of LODDS is superior to that of the N descriptor and LNR for estimating OS 25 . We showed that LCC patients were more in LODDS ≥ −0.9 sub, which might be related to the different sensitivity to immunotherapy between LCC and RCC, and this was not observed in N stage and LNR subs.…”
Section: Discussionsupporting
confidence: 65%
“…Ye et al reported similar results in esophageal carcinoma, demonstrating that the prognostic efficacy of LODDS is superior to that of the N descriptor and LNR for estimating OS. 25 We showed that LCC patients were more in LODDS ≥ −0.9 sub, which might be related to the different sensitivity to immunotherapy between LCC and RCC, and this was not observed in N stage and LNR subs. Above all, these indicate that the discriminative power of LODDS is superior to N stage and LNR.…”
Section: Discussionmentioning
confidence: 63%
“…For the N descriptor, the lymph node (LN) is based on the lymphatic region involved without any information of the number of dissected LNs (NDLN) and the number of positive LNs (NPLN) [ 7 ]. The log odds of positive LNs (LODDS) is a novel LN descriptor that has advantages over the N stating descriptor of the TNM system in many malignancies, including rectal cancer [ 8 ], gallbladder cancer [ 9 ], gastric adenocarcinoma [ 10 ], cervical cancer [ 11 ], and esophageal carcinoma [ 12 ]. LODDS is calculated using the following formula: ln([NPLN + 0.5]/[NDLN-NPLN + 0.5]).…”
Section: Introductionmentioning
confidence: 99%
“…The log odds of positive lymph nodes (LODDS), defined as the natural logarithm of the ratio of a metastatic lymph node to a non-metastatic lymph node, has been emerging as an essential prognostic factor for cancer prognosis, including colon cancer ( 9 ), breast cancer ( 10 ), oral squamous cell ( 11 ), lung squamous cell carcinoma ( 12 ), and so on. For esophageal carcinoma, LODDS also exhibits better discrimination power in risk stratification than N descriptor and positive lymph node ratio (LNR) ( 13 ). Ye and his colleagues also developed a nomogram based on the Surveillance, Epidemiology, and End Results (SEER) database, which integrated age, gender, histological grade, T stage, and LODDS as the risk factor, with a C-index of 0.647 ( 13 ).…”
Section: Introductionmentioning
confidence: 99%